Pengaruh Budaya Lamaholot Dalam Ruang Kota Larantuka - Subanpulo, Oktovianus Sila Wuri (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
Nusa Tenggara Timur Province has a diverse ethnicity with various language, tradition, and cultural background. Spread across the province, each ethnic group are divided into sub tribes/family groups known as clans. Larantuka, the capitol of East Flores is a part of the Lamaholot tribe. In this city exists groups of settlements based on ethnicity consisting of the Lewo Waibalun, Lewo Lere, Lewo Balela, Lewo Larantuka and Lewo Lebao. These traditional communities includes the low, middle and high class, and are constructed by association of tribe, religion and race. Larantuka, which used to be a kingdom, had a distinguishable pattern as a Lamaholot traditional settlement, which had been occupied by the Kakang Nuba faction (King’s advisors). As time changes the way of living of the people, several changes are apparent in the pattern of settlements and their infrastructures which forms the Lamaholot community structure in Larantuka. There is a concern that this change will, sooner or later, affect the settlement environment quality, and even eliminate the identity as a Lamaholot traditional settlement and the city’s historical potential.